Analysis of Factors Influencing the Selection of Maternal Birth Aid during the Covid-19 Pandemic in the Nambo Community Health Center Area - Windarsi Daiyeng; Siti Kholisah (Journal for Research in Public Health, 2022)
Background: Maternal and Child Health Problems (MCH) is still a health problem in Indonesia. The Maternal Mortality Rate and Infant Mortality Rate in Indonesia are still high with the number of maternal deaths annually reaching 305 per hundred thousand live births. The coverage of delivery assistance that is still not according to the target given by the government is one of the problems that occurs in several regions in Indonesia, based on data from the 2014 Indonesian Health Profile that the national coverage is 88.68%, where this figure has not been able to meet the target of 90%. This study aims to determine the factors that influence the selection of maternity birth attendants during the COVID-19 pandemic in the Nambo Health Center area. This research is a descriptive qualitative research with a case study design. Based on the results of the research, the informant factor in the decrease in the selection of maternity birth attendants during the covid-19 pandemic in the Nambo Health Center area and choosing a traditional birth attendant as a birth attendant, namely the informant's inadequate knowledge, high trust in the services provided by the shaman and low income and inadequate education of informants is a factor in informants choosing traditional birth attendants as birth attendants. Based on the results of the study, the informants stated that the fees set by the traditional birth attendant were not expensive, so that the community was more dominant in giving birth to the traditional birth attendant. It is hoped that health workers will be able to further promote assistance by health workers in the form of counseling in health activities held such as integrated health center, PKK and approach the community to build trust from the community which will bring the community closer to health workers, especially midwives. Methods: The design of this research is descriptive qualitative. Informants were taken using a purposive sampling technique that met the inclusion and exclusion criteria as many as 3 people (1 midwife, 1 mother giving birth at the public health center, 1 giving birth at a traditional healer). Data collection techniques through in-depth interviews and documentation with informants. Qualitative data analysis techniques using Data Reduction, Data Presentation, Conclusion Drawing / Verification. Results: The results showed that the choice of place of delivery by health workers was 67.33%, still below the 100% target. Constraints faced such as the lack of public trust in health workers in helping childbirth so that pregnant women prefer traditional healers to give birth. Government support, such as holding cross-sectorial meetings to make a jointly signed decision that traditional birth attendants are not allowed to assist in childbirth alone but must coordinate with health workers. Conclusion: Based on the results of the study, it was concluded that the delivery achievement by health workers was still below the national target of 100%. It is recommended that village midwives should work together with village cadres so that they can report data on pregnant women in the village so that they can detect health problems for pregnant women by conducting integrated ANC examinations and ensuring that every pregnant woman has a MCH handbook.